2019
DOI: 10.1111/eva.12790
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox in cancer: Is bigger really better?

Abstract: While obesity is widely recognized as a risk factor for cancer, survival among patients with cancer is often higher for obese than for lean individuals. Several hypotheses have been proposed to explain this “obesity paradox,” but no consensus has yet emerged. Here, we propose a novel hypothesis to add to this emerging debate which suggests that lean healthy persons present conditions unfavorable to malignant transformation, due to powerful natural defenses, whereby only rare but aggressive neoplasms can emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Methodological errors such as selection bias, reverse causality, and collider bias are also assumed to be the cause [ 26 , 28 ], although a study designed to minimize the biases found that the paradox is conserved even after correction [ 10 ]. Ujvari et al [ 29 ] suggested that the immune system, which fights indolent types of precancerous colonies before they differentiate into cancer works more favorable in normal-weight people than obese people. Therefore, the proportion—not the absolute number—of aggressive cancers may be lower in cancer patients with obesity than normal weight, leading to a seemingly better survival in the former [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methodological errors such as selection bias, reverse causality, and collider bias are also assumed to be the cause [ 26 , 28 ], although a study designed to minimize the biases found that the paradox is conserved even after correction [ 10 ]. Ujvari et al [ 29 ] suggested that the immune system, which fights indolent types of precancerous colonies before they differentiate into cancer works more favorable in normal-weight people than obese people. Therefore, the proportion—not the absolute number—of aggressive cancers may be lower in cancer patients with obesity than normal weight, leading to a seemingly better survival in the former [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The "obesity paradox" is an intriguing concept in linking adiposity and cancer prognosis (Park et al, 2018;Ujvari et al, 2019). Interestingly, there seems to be a link between obesity and the tumor microenvironment, particularly the immune parameters and mechanisms, especially in CD8 T cells (Turbitt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to understanding the TME, recent studies have also demonstrated the importance of patient-associated factors that can impact the response to immunotherapy, such as body composition (fat mass, fat-free mass and muscle quality), sex, ethnicity, age, habits (e.g., smoking, alcohol use, physical activity), past illnesses (immune history) and gut microbiota [ 23 , 24 , 369 – 373 ]. Obesity, currently considered a pandemic, is characterized by changes in the physiology of the entire body.…”
Section: Immunotherapy Cancer and Obesitymentioning
confidence: 99%